Ameliorating Effect Of Extracts Of Alstonia Scholaris & Boerhaavia Diffusa In FCA Induced Arthritis In Wistar Albino Rats (International Journal of Food and Nutritional Sciences, 2022)
AIM- The aim of the present investigation is to study the anti-arthritic activity of bark of Alstonia scholaris & root of Boerhaavia diffusa in FCA induced arthritis in Wistar albino rats. MATERIAL & METHODS- All the plant materials were dried under shade and subjected to coarse powder for extraction process. Accurately weighed quantity of bark powder of Alstonia scholaris were extracted using 95 % ethanol & methanol by soxhlet apparatus for 72 h. Qualitative chemical tests of ethanolic & methanolic extracts were subjected to various chemical tests to detect various phytoconstituents. The acute oral toxicity studies were carried out according to the guidelines set by the Organization for Economic Co-operation and Development (OECD), revised draft guideline 423. The severity of adjuvant arthritis was quantified by measuring the volume of the hind paw using Plethysmograph. Paw volume (ml) was measured at 0 days and thereafter 4, 8, 12, 16 and 21 days of FCA post-inoculation. On the 21st day after arthritis induction, rats were anaesthetized with ether and blood samples were collected into Ethylenediamine tetra-acetic acid (EDTA)-coated tubes from retro orbital junction. RESULTS- The preliminary phytochemical analysis revealed that different active constituent present in different extracts such as carbohydrates, proteins, amino acids, fat, oils, steroids, terpenoids, glycosides, alkaloids, tannins and other phenolics compounds. The cut off value of 200 and 1/5 dose double of 400 mg/kg were selected for anti-arthritic activity. The assessment made on the 21st day showed that the A. scholaris treatments at both doses (low and high) had moderately significant and highly significant effect and reduced (p< 0.01& p